PELAKSANAAN PEMBINAAN WARGA BINAAN MENURUT UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - Nandito Hutagalung (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTThe Penitentiary is a place for guidance to the assisted residents. This is contained in Article 1 paragraph (3) of Law Number 12 the Year 1995, namely